DEVELOPMENT IN HIMALAYA’S AND LANDSLIDE DISASTER MANAGEMENT: A SPECIAL REFERENCE OF HIMACHAL PRADESH - Pandey, Deep Narayan; Choubey, Awadh Narayan; Saini, Satish Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Landslides is a major risk in India that presents a risk to human lives, livelihood and property. The level of destruction caused by them is unimaginable. Therefore, it is very necessary to do proper management of such risks. Also, development is very necessary for region’s overall growth. But in major instances, these developmental projects and activities are the major causes of such hazards. Therefore, this paper highlights the developmental projects and their contribution in Himachal Pradesh as well the extent to which they hamper the ongoing development of Himachal Pradesh by increasing the frequency and magnitude of risks like landslides. Also, this paper suggests some mitigation strategies of landslide disaster management as given in State Disaster Management Plan. Also, some of the key initiatives are also discussed which can be included in accordance with disaster management.